Non-Fermi-liquid to Fermi-liquid transports in iron-pnictide Ba(Fe1−xCox)2As2 and the electronic correlation strength in superconductors newly probed by the normal-state Hall angle. (28th March 2017) - Wang, L M; Wang, Chih-Yi; Zen, Sha-Min; Chang, Jin-Yuan; Kuo, C N; Lue, C S; Chang, L J; Su, Y; Wolf, Th; Adelmann, P
Abstract: Electrical transports in iron-pnictide Ba(Fe1− x Co x )2 As2 (BFCA) single crystals are heavily debated in terms of the hidden Fermi-liquid (HFL) and holographic theories. Both HFL and holographic theories provide consistent physic pictures and propose a universal expression of resistivity to describe the crossover of transports from the non-Fermi-liquid (FL) to FL behavior in these so-called 'strange metal' systems. The deduced spin exchange energy J and model-dependent energy scale W in BFCA are almost the same, or are of the same order of several hundred Kelvin for over-doped BFCA, which is in agreement with the HFL theory. Moreover, a drawn line of W /3.5 for BFCA in the higher-doping region up to the right demonstrates the crossover from non-FL-like behavior to FL-like behavior at high doping, and shows a new phase diagram of BFCA. The electronic correlation strength in superconductors has been newly probed by the normal-state Hall angle, which found that, for the first time, correlation strength can be characterized by the ratios of T c to the Fermi temperature T F, J / T F, and the transverse mass to longitudinal mass.